Investigation of The Effects of Carbon Dioxide from Paper Combustion on Temperature Changes - 'Ain, Khaula Noorul; Prima, Eka Cahya (Faculty of Science and Education, UIN Walisongo Semarang, 2025)
This study explores the relationship between carbon dioxide (CO₂) concentration from paper combustion and temperature changes using a greenhouse effect simulation. Two desiccators were used: desiccator A with an LED lamp as an additional heat source, and desiccator B without an external heat source. The results showed that an increase in CO₂ in desiccator A significantly raised the temperature, demonstrating CO₂'s role in heat retention. However, in desiccator B, a temperature drop occurred due to the endothermic effects of paper combustion and water evaporation. These findings highlight the importance of external energy sources in manifesting the greenhouse effect and explain the complexity of the thermodynamic processes involved. This study contributes to a deeper understanding of CO₂-induced temperature changes and its relevance to global warming. The experiment can be used as an effective educational tool to introduce students to the greenhouse effect concept.